EMERGENCY COMMUNICATION SYSYTEM FOR NATURAL DISASTER USING MANET - Babu J, Dilish; Kumar, Dr. S Mohan (IJRDO -Journal of Computer Science Engineering, 2016)
Regular fiasco stricken numerous ranges of world consistently, effectiveness of salvageoperation is exceptionally basic to life sparing of caught casualties. Be that as it may, cell correspondenceframework is generally slammed when calamity hits a territory which makes coordination extremelytroublesome among salvage volunteer groups. Tragically a large portion of existing crisis correspondenceframework may not be plausible. In this paper, we proposed idea of half and half cell MANET engineeringwhich utilize working cell base station in the event that they are not slammed. We additionally give adirecting plan for this crisis situation which effectively uses accessible correspondence and vitality assets ofgadgets. The proposed crisis correspondence design knows about portability of gadgets furthermore bolsterself sorting out component of MANET. This correspondence model can be setup in catastrophe hit zoneinside couple of hours